Macro and micro of external finance premium and monetary policy transmission - Carlo Altavilla; Refet S. Gürkaynak; Rogier Quaedvlieg (European Central Bank (ECB), 2024)
We establish basic facts about the external finance premium. Tens of millions of individual loan contracts extended to euro area firms allow studying the determinants of the external finance premium at the country, bank, firm, and contract levels of disaggregation. At the country level, the variance in the premium is closely linked to sovereign spreads, which are important in understanding financial amplification mechanisms. However, country level differences only explain half of the total variance. The rest is predominantly attributed to variances at the bank and firm levels, which are influenced by the respective balance sheet characteristics. Studying the response of the external finance premium to monetary policy, we find that balance sheet vulnerabilities of banks and firms strengthen the transmission of policy measures to financing conditions. Moreover, our findings reveal an asymmetrical effect contingent upon the sign and type of the policies. Specifically, policy rate hikes and quantitative easing measures exert a more pronounced impact on lending spreads, further magnified through their repercussions on the external finance premium.
Keywords: E44; E58; F45; G15; G21; 330; External finance premium; financial accelerator; euro area; loan pricing